1993
DOI: 10.1063/1.465590
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of global coupling in oscillatory chemical reactions

Abstract: The effects of global coupling through the gas phase in oscillatory surface chemical reactions are investigated using a model which represents the complex Ginzburg–Landau equation with an additional integral term. Depending on the parameters of the model, global coupling is found to have either a synchronizing or desynchronizing effect. Respectively, the breakdown of global coupling requires the presence of strong supercritical inhomogeneities or spontaneously occurs in a uniform system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(40 citation statements)
references
References 7 publications
1
39
0
Order By: Relevance
“…In heterogeneous catalysis mixing in the gas phase produces a global coupling because a consumption of reactants at one location causes changes in conditions at all locations of the system. [24][25][26][27] Global coupling through an external control or an integral constraint has also been a͒ Electronic mail: eiswirth@fhi-berlin.mpg.de investigated in heterogeneous catalytic systems. [28][29][30] Pattern formation in semiconductors is to a large extent due to local diffusion and global constraints due to the current circuit.…”
Section: Introductionmentioning
confidence: 99%
“…In heterogeneous catalysis mixing in the gas phase produces a global coupling because a consumption of reactants at one location causes changes in conditions at all locations of the system. [24][25][26][27] Global coupling through an external control or an integral constraint has also been a͒ Electronic mail: eiswirth@fhi-berlin.mpg.de investigated in heterogeneous catalytic systems. [28][29][30] Pattern formation in semiconductors is to a large extent due to local diffusion and global constraints due to the current circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Kinks and traveling Bloch walls are elementary wave patterns under forcing conditions. Instabilities of kinks lead to backfiring and development of intermittent regimes with reproduction of amplitude defects [15,16,17]. Transverse instabilities of nonequilibrium planar Bloch walls give origin to the Bloch turbulence [6].…”
Section: The Forced Complex Ginzburg-landau Equationmentioning
confidence: 99%
“…2 (a)). Inside this region, kinks (n = 1) and Bloch walls (n = 2) traveling at a constant velocity are possible (see [12,15,16]). Moreover, wave trains formed by periodic sequences of such phase fronts can also be observed there.…”
Section: The Forced Complex Ginzburg-landau Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the kind of feedback, global coupling may either stabilize or destabilize the uniformly oscillating situation through symmetry breaking [54]. Systematic analysis of the kinds of pattern formation in an oscillatory medium with global coupling was performed with a model system, the modified Ginzburg-Landau equation, whose characteristic features are, however, of general validity [55]. It was shown that global coupling may, among others, modify or even suppress turbulent behavior.…”
Section: Overview Of the Theoretical Backgroundmentioning
confidence: 99%